PEMODELAN NUMERIK ALIRAN TAK JENUH UNTUK EVALUASI INFLOW DAN STABILITAS LERENG TAMBANG TROPIS DI KALIMANTAN SELATAN - Jarwanto, Jarwanto; Arie Noor Rakhman (Yayasan Nusantara Hasana Berdikari, 2026)
Open-pit mining operations in South Kalimantan, Indonesia, face complex geohydrological challenges due to extreme tropical rainfall and heterogeneous overburden stratigraphy. This study aims to evaluate the role of unsaturated flow (vadose zone) in predicting mine inflow and slope stability, and to assess the limitations of conventional approaches that consider saturated flow conditions only. One-dimensional (1-D) and two-dimensional (2-D) numerical models were developed using the Finite Element Method (FEM) based on the Richards equation to quantify infiltration dynamics and wetting front propagation under episodic rainfall, compare unsaturated model outputs with conventional saturated models, and analyze the sensitivity of Soil Water Retention Curve (SWRC) parameters and unsaturated hydraulic conductivity functions K(θ). The governing equations were solved using a Newton–Raphson iterative scheme to handle the strong nonlinearity of hydraulic functions. The results demonstrate that unsaturated flow models represent transient hydrological responses more accurately than saturated models, which tend to underestimate early-stage inflow. Under extreme rainfall scenarios analogous to the January 2021 regional flooding event, the wetting front reached critical depths within 2–5 days, accompanied by a rapid increase in pore water pressure that may compromise slope stability. Sensitivity analysis indicates that the van Genuchten parameters (α and n) and saturated hydraulic conductivity (K_s) dominate model output uncertainty, particularly within intermediate moisture ranges typical of lateritic and alluvial materials. These findings highlight the necessity of integrating coupled unsaturated–saturated flow modeling with field-based measurements to support effective dewatering design and slope risk mitigation in high-rainfall open-pit mining environments.